PENGARUH WAKTU DAN MEDIA SIMPAN TERHADAP VIABILITAS BENIH MATOA (Pometia pinnata J.R. Forster & J.G. Forster) - Arif Irawan; Iwanuddin Iwanuddin (Jurnal Pemuliaan Tanaman Hutan, 2019)
Matoa (Pometia Pinnata J.R. Forster & J.G. Forster) is one of potential multipurpose tree species for forest and land rehabilitation program in North Sulawesi. Limited information on the technique of cultivation of matoa often become an obstacle for development, especially seed storage techniques because of all the seed are not always directly sown after collection. This study aims to determine the effect of time and storage media on the viability of matoa seeds. The design used in this study was complete randomly design arranged in factorial, consisting of (two) main factors : 1) storage time and 2) storage media. The storage time consists of three  levels : 5 days, 10 days and 15 days. Storage media consists of four levels : aluminium foil, calico cloth, cocopeat and without storage media. The results showed that the aluminium foil is the best storage media that can be used to store the matoa seeds up to 15 days.